THU0401 WOMEN WITH SPONDYLOARTHROPATHIES HAVE HIGHER DISEASE BURDEN ACCORDING TO RAPID3 COMPARED TO MEN, BUT THERE IS NO GENDER DIFFERENCES ACCORDING TO A MODIFIED ASDAS-CRP. (June 2019) - Riad, Mariam; Blasco-Blasco, Mar; Gevorgyan, Ofelya; Castrejon, Isabel
Abstract : Background: Women with Spondyloarthropathies (SpA) may be late or under-diagnoses due to a less typical presentation than in men, with a more peripheral clinical manifestation. Although some studies have suggested a higher burden of disease in women 1, 2, others did not confirm these differences 3, 4 . In addition, women present higher scores for pain and fatigue, which may influence the BASDAI (Bath Ankylosing Spondylitis Disease Activity Index) score 5 . Objectives: To evaluate possible gender differences in clinical presentation and disease severity in men and women with SpA in routine care at one academic center. Methods: All patients complete a Multidimensional Health-Assessment Questionnaire (MDHAQ) as part of their routine care. It includes physical function (FN) (0-10), three 0-10 visual analogue scales (VAS) for pain (PN), patient global estimate (PATGL), and fatigue (FT), RADAI self-reported painful joints, and morning stiffness (MS). Patients with SpA (ICD10 codes) were included: ankylosing spondylitis (AS), psoriatic arthritis (PsA), undifferentiated, and inflammatory bowel disease associated (IBD). Data extracted were clinical presentation, treatment and laboratory tests including C-reactive protein (CRP), HLA-B27 (Human leukocyte antigen), and erythrocyte sedimentation rate (ESR). Composite indices, RAPID3 (0-30) previously validated in SpA, as the sum of 0-10 scores for FN, PN, and PATGL, and a modified ASDAS-crp using a " back pain" score derived from RADAI neck, back and hips; a "peripheral pain" score derived from the remaining RADAI joints; and MS in minutes were also included. Demographic and clinical characteristics were compared according to gender. Results: 190 patients were included, 60% males and 40% females, with no differences in age, disease duration, and treatment. Men had significantly more frequent inflammatory back pain. Patient global assessment and pain scores were significantly higher in women versus men resulting in a higher RAPID3 (moderate disease severity in both groups). Axial, peripheral pain, morning stiffness and laboratory data did not show differences by gender, and as a result ASDAS-CRP was similar between men and women, with a value corresponding to moderate disease activity (Table). Conclusion: Women with SpA have higher RAPID3 scores than men, in contrast to a modified ASDAS-CRP based on scores from the MDHAQ which did not show gender differences. These data suggest that RAPID3 scores in women may be attributable in part to a gender bias rather than clinical severity and a careful interpretation in the context of gender is necessary. References: [1] Ann Rheum Dis. 2013; 72(7):1221-4. [2] Reumatol Clin. 2013; 9(4):221-5. [3] Rheumatology (Oxford). 2014; 53(5):875-81. [4] Clin. Rheumatol. 2015; 34(2):285-93.2015. [5] Ann Rheum Dis. 2017; 76: Suppl.2. 657-658. Disclosure of Interests: None declared